Prognostic significance of sarcopenia and decreased relative dose intensity during the initial two cycles of first-line sunitinib for metastatic renal cell carcinoma. (19th May 2021) - Lee, Chan Ho; Ku, Ja Yoon; Seo, Won Ik; Park, Young Joo; Chung, Jae Il; Kim, Wansuk; Park, Tae Yong; Ha, Hong Koo
Abstract : Targeted therapy for metastatic renal cell carcinoma (mRCC) treatment requires the identification of clinically important factors that can predict the therapeutic effect. We retrospectively investigated the prognostic roles of pre-treatment sarcopenia and relative dose intensity during the initial two cycles (2c-RDI) of sunitinib treatment in patients with mRCC. In total, 41 (52.6%) patients were classified as having sarcopenia and 16 (20.5%) patients were classified with low 2c-RDI at <75%. The mean dose reduction during sunitinib treatment was higher for sarcopenic than for non-sarcopenic patients. The median progression-free survival (PFS) and overall survival (OS) were significantly shorter in sarcopenic patients with low 2c-RDI (n = 14, 17.9%) than in non-sarcopenic patients with high 2c-RDI (n = 35, 44.9%). Multivariate analysis identified sarcopenia and low 2c-RDI as poor prognostic factors for PFS and OS. Our findings provide new insights into the prognostic role of sarcopenia and 2c-RDI for targeted therapy in mRCC.